PO 18117 - Epidemiological study of calcaneal fractures - Christovan Ribeiro, Evandro Junior; Beletato, Rafael Maurício; Damião Prata, Sérgio; Rizzo, Marco Antônio (Scientific Journal of the Foot & Ankle, 2019)
Objective: To analyze the epidemiological characteristics of patients with calcaneal fractures. Methods: We included 181 medical records of patients diagnosed with calcaneal fracture from September 2008 to August 2015. The analyzed parameters were patient characteristics, trauma mechanism, associated fractures, open or closed fracture, time of day, season, preoperative radiographic evaluation, Essex-Lopresti and Sanders classification, treatment type and technique used. Results: Of the patients included in the sample, 84% were white, and 58.1% did not attend high school. A total of 89.5% of the patients with calcaneal fracture were men, and the mean participant age was 43 years. No significant difference was found in laterality, 8.8% were bilateral fractures, and 74.6% of the fractures occurred in the afternoon. The most frequent trauma mechanism was fall from height (90.1%). According to the Sanders classification, type 3 AC fractures occurred in 41.6% patients. Conclusion: Calcaneal fractures primarily affected working-age men, especially construction workers, who did not attend high school. The most frequent trauma mechanism was fall from height.